Modification of national OSCE due to COVID-19-Implementation and students' feedback - Hytonen H; Napankangas R; Karaharju-Suvanto T; Evasoja T; Kallio A; Kokkari A; Tuononen T; Lahti S (Wiley, 2022)
Aim The aims were to describe the development of a modified national online OSCE during COVID-19 and assess related student feedback.Material and methods The modified online OSCE comprising of eight question entities was organised simultaneously in all four dental institutes of Finland using the Moodle virtual learning environment. All fourth-year students (n = 179) attended the examination online at home. Student feedback was collected via an anonymous questionnaire with multiple-choice questions and open-ended questions concerning attitudes towards the modified online OSCE, as well as content and usability of the question entities in the examination. Means and standard deviations were calculated for multiple-choice questions. Content analysis was used for open-ended questions.Results Of 179 students, 119 (66%) consented to the study. Students experienced they had received adequate information (mean 3.8; SD 1.2), had a positive attitude before the examination (4.0; 1.0) and found the practice test useful (3.7; 1.1) (range 1-5). Technical implementation (2.7; 0.7) and the difficulty of the questions (2.9; 0.6) (range 1-4) were found to be good. The teaching students received during their studies was sufficient (3.2; 0.5) (range 1-4). Content (mean 3.2; 0.4) and usability (2.9; 0.4) of the question entities were good (range 1-4). The themes arising from open-ended questions were importance and practicality of the topic (in questions) in relation to the work of a dentist and gratitude for the rapid conversion of the OSCE into an online examination despite COVID-19. The themes arising from negative experiences included difficulties in completing the examination within the time allocated, and dissatisfaction with the model answers provided after the examination.Conclusion The positive student feedback towards the modified online OSCE encourages including an online examination to complement the traditional OSCE.